Uniform Scattering Power for Monitoring the Spilled Oil on the Sea - Jiang Xu; Weixian Qian; Qian Chen; Guohua Gu; Yingcheng Lu; Yang Zhou (IEEE Photonics Journal, 2018)
The physical model of polarized light scattered from oil film had been analyzed, which helped us to derive the Mueller matrix of uniform scattering. The parameter, uniform scattering power (USP), has been proposed to analyze the scattering intensity of regular, smooth, and raised surfaces in the observation direction. USP could overcome the influence of angles in oil spill detection and provide us with better monitoring signals. The actual spilled oil had been measured by this model, and the oil film could been accurately identified at various angles.